Atomistic understanding on friction behavior of amorphous carbon films induced by surface hydrogenated modification. (August 2019) - Li, Xiaowei; Wang, Aiying; Lee, Kwang-Ryeol
Abstract: Friction behavior of self-mated amorphous carbon (a-C) films with hydrogenated surface were investigated by reactive molecular dynamics simulation. Results revealed that compared to the hydrogenated a-C (a-C:H) films, hydrogenating the a-C surface only improved the friction property drastically while not deteriorating the intrinsic properties of a-C films. The analysis of interfacial structure demonstrated that being different with a-C:H cases, the competitive relationship between the stress state of H atoms and interfacial passivation caused by H and C-C structural transformation accounted for the evolution of friction coefficient with surface H content. This discloses the friction mechanism of a-C with surface hydrogenated modification and provides an approach to functionalize the carbon-based films with combined tribological and mechanical properties for specific applications. Graphical abstract: Image 1 Highlights: Dependence of friction behavior of a-C on surface passivation degree were explored. The a-C with surface hydrogenated modification exhibited excellent friction property. Tailoring surface H content obtained better friction property than oil lubrication. Friction mechanism of a-C with surface modification was different with that of a-C:H. H stress state and interfacial passivation accounted for the friction behavior.